Carbetocin versus oxytocin in primigravida for active management of third stage of labor: a prospective study - Patil, Ambika; Puram, Mounika; Thobbi , Vidya A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Postpartum haemorrhage (PPH) stands as a prominent global contributor to maternal mortality. Oxytocin's short half-life and heat sensitivity pose challenges in resource-limited areas. Carbetocin, not requiring cold storage, is utilized in third-stage labor management. Consequently, this study aimed to compare the effectiveness of carbetocin with oxytocin in third-stage labor management. Methods: In this prospective study of 200 primigravida patients, group A received heat-stable carbetocin (100 μg), while group B received oxytocin (10 IU) postpartum. Primary outcome such as mean blood loss in ml and Secondary outcomes such as proportion with blood loss >500 ml, need for uterotonic agents, blood transfusion, surgical PPH management, and drop in haemoglobin after 48 hours were recorded and compared. Results: Groups A and B, comparable in age, blood pressure, and mild anaemia, exhibited significant gestational age differences (p<0.0001). Group B had higher mean blood loss (377.68 ml) than group A (345.34 ml) with a significant p=0.0118*. Side effects showed no differences among groups. Postpartum, group B saw a significant 7% incidence of haemorrhage compared to none in group A (p=0.0071). Conclusions: Carbetocin showed superiority over oxytocin in the active management of third stage of labor, exhibiting a statistically significant reduction in PPH incidence and decreased requirement for additional uterotonic drugs.